KEBUTUHAN PERAWATAN ORTHODONSI BERDASARKAN INDEX OF ORTHODONTIC TREATMENT NEED PADA SISWA SMP NEGERI 1 TARERAN - Wilar, Liefany Anastasia; Rattu, A. J. M.; Mariati, Ni Wayan (Universitas Sam Ratulangi, 2014)
Abstract: Malocclusion according to World Health Organization (WHO) is a defect or functional distruption that can be a hampered to a physical and emotional health from patient who needs treatment. The aim of this study is to know the needs of orthodontic treatment of students in SMPN 1 Tareran ages 13-14 years old according to IOTN. Index of Orthodontic Treatment Need consisted of two parts which are Aesthetic Component (AC) and Dental Health Component (DHC). This is a descriptive study, has done in SMPN 1 Tareran Rumoong village on March 2014. The population of this study is all the students of SMPN 1 Tareran ages 13-14 years old totaled 155 students and only 61 students included in the sampling frame. These sample observed using AC and DHC according to IOTN. The result of the study showed that according to AC (73,77%) don’t need treatment or need minor treatment, (22,95%) need a borderline treatment and (3,28%) really need treatment. According to DHC (16,39%) don’t need treatment or need minor treatment, (18,04%) need a borderline treatment and (65,57%) really need treatment. Keywords: Malocclusion, Index of Orthodontic Treatment Need, Aesthetic Component, Dental Health Component. Abstrak: Maloklusi menurut World Health Organization (WHO) adalah cacat atau gangguan fungsional yang dapat menjadi hambatan bagi kesehatan fisik maupun emosional dari pasien yang memerlukan perawatan. Tujuan penelitian ini untuk mengetahui kebutuhan perawatan orthodonsi siswa SMP Negeri 1 Tareran usia 13-14 tahun berdasarkan IOTN. Index of Orthodontic Treatment Need terdiri dari dua bagian yaitu Aesthetic Component (AC) dan Dental Health Component (DHC). Penelitian ini bersifat deskriptif, dilakukan di SMP Negeri 1 Tareran desa Rumoong pada bulan Maret 2014. Populasi penelitian ini yaitu seluruh siswa SMP Negeri 1 Tareran usia 13-14 tahun yang berjumlah 155 siswa dan hanya 61 siswa yang termasuk dalam sampling frame. Sampel kemudian diperiksa menggunakan AC dan DHC berdasarkan IOTN. Hasil penelitian menunjukkan bahwa berdasarkan AC (73,77%) tidak atau butuh perawatan ringan, (22,95%) butuh perawatan borderline dan (3,28%) sangat butuh perawatan. Berdasarkan DHC (16,39%) tidak atau butuh perawatan ringan, (18,04%) butuh perawatan borderline dan (65,57%) sangat butuh perawatan. Kata kunci: Maloklusi, Index of Orthodontic Treatment Need, Aesthetic Component, Dental Health Component.